Charting Your Course: A Roadmap to Select a Review Type for Your Research Journey - Jannette Bradley; Barbara E. Ruggeri; Karen L. Hanus (Journal of Patient-Centered Research and Reviews)
Summarizing evidence found in the literature is an important component of the research process. Researchers who undertake a project to summarize evidence will hopefully have their results published in a peer-reviewed journal. However, there are dozens of review types. Choosing the right review type is not always straightforward. The researcher’s process is much like a journey that requires careful charting to avoid wrong turns and wasted resources and potentially ensure that somebody else can replicate the process. Depending on the goal/destination, the researcher/traveler needs to choose the proper review type, or chart the right course, to select their route and ensure that they are headed in the desired direction. We have summarized seven of the most prevalently used review types and provided a purpose-driven roadmap of the review types to help researchers. A librarian can help researchers further refine which review type is the most suitable for their research.